The psychology of romantic relationships: motivations and mate preferences - Tartakovsky, Eugene (Frontiers in Psychology, 2023)
This study investigates motivations to engage in romantic relationships. We examine the structure of romantic motivations and their connections with personal values and mate preferences. The study was conducted in Israel among young men and women looking for a romantic partner (n = 1121, 40% male, age 18-30). Data analysis demonstrated that basic romantic motivations form a circumplex that may be partitioned into four higher-order romantic motivations: love and care, family and children, status and resources, and sex and adventure. The romantic motivational clusters formed a meaningful pattern of connections with higher-order values, thus confirming that context-specific motivations are derived from general motivational goals expressed in values.Personal value preferences and romantic motivations predicted the sought-after partner characteristics over and above sociodemographic variables. Values were indirectly (through romantic motivations) and directly connected to mate preferences. The study advances our understanding of romantic relationships among young people and opens new directions for research and counseling.